Effect of heat exposure on the growth and developmental competence of bovine oocytes derived from early antral follicles - Kohei Kawano; Kenichiro Sakaguchi; Chelenga Madalitso; Nattapong Ninpetch; Shintaro Kobayashi; Eri Furukawa; Yojiro Yanagawa; Seiji Katagiri (Scientific Reports, 2022)
Abstract In dairy cows, low fertility caused by summer heat stress continues into the cooler autumn season. This can be caused by impaired oocyte quality in small growing follicles during summer. Here, we subjected oocyte–cumulus–granulosa complexes (OCGCs) derived from early antral follicles (0.5–1 mm) to in vitro growth (IVG) culture under two different temperature settings (the control and heat shock groups), and evaluated effects of heat exposure on growth and developmental competence of oocytes, factors affecting the developmental competence of oocytes (steroidogenesis of granulosa cells, oxidative stress in oocytes, and cell-to-cell communication between oocytes and somatic cells). Oocyte diameters after culture were smaller in the heat shock group. Although nuclear maturation and cleavage rates were similar between the groups, blastocyst rates were lower in the heat shock group (0.0%) than in the control group (27.7%), and reduced glutathione (GSH) levels in oocytes were lower in the heat shock group. Supplementation of cysteine, which stimulates GSH synthesis, increased GSH level and improved blastocyst rate of heat shocked oocytes (27.9%). These results suggest that heat exposure impairs the growth and developmental competence of oocytes in early antral follicles through GSH depletion, which can induce low fertility during summer and the following autumn.